G225(P) Disorders of sexual differentiation clinic, oxford, uk. (12th March 2018) - Ahmed, P; Romero, R; Ryan, F
Abstract : Aim: Disorders of sexual differentiation (DSD) are a heterogeneous group of genetic disorders with a mismatch of chromosomal, gonadal and phenotypic sex. The John Radcliffe Hospital is one of the largest and few DSD centres in the country, providing a highly specialised multi-disciplinary team service. The aims were to analyse the patient cohort with DSD under the care of the hospital, including their diagnoses, medical and surgical interventions and ascertain the strengths of the DSD service provided, and how the service can be improved to meet UK guidance on a DSD clinic. Methods: A retrospective review was conducted from 2012–2016 to identify the diagnoses and medical and surgical interventions of the DSD patients. The DSD clinic service was compared with UK guidance. Results: 46 patients were identified with 28 males, 18 females and 91% of patients having attended the DSD MDT clinic at least once. The average age of patients was 7.5 years. The number of patients with a genetic diagnosis was 96% and of those with a confirmed diagnosis, the most common diagnoses were partial androgen insensitivity syndrome (27%) and congenital adrenal hyperplasia (25%). The majority of patients were diagnosed by ambiguous genitalia- 85%. Endocrinological problems were identified in 43% of patients, requiring input in the form of hormone replacement. Surgical intervention was required in 89% of patients, with hypospadias repair being the most common procedure. Currently, the DSD clinic involves input from surgery/urology, endocrinology and psychiatry, in order to devise a clinical management plan, as per UK guidance. Further areas for improvement include an endocrinologist to act as 'clinical lead' for newborns, improved links to adult services and an annual MDT meeting to review and discuss the patients and review the DSD clinic performance. Conclusions: The DSD MDT clinic meets many of the UK requirements. Importantly, an MDT clinic allows families to retrieve all results in one day with liaison between specialties for holistic care, and minimises time taken off work and school thus improving attendance, whilst forming a support group in the waiting room. Therefore, despite being a costly service, it is certainly worth continuing.